FINANCIAL FEASIBILITY ANALYSIS OF SMALL AND MEDIUM ENTERPRISES: A CASE STUDY OF UD. MANGGENG FOOD IN MANGGENG DISTRICT, SOUTHWEST ACEH REGENCY - Bagio; Cut Nidawati; Akhmad Baihaqi; Sri Handayani; Qhisthina Atikah; Safrika; Liston Siringo Ringo; Nana Ariska; Alfis Yuhendra (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study analyzes the financial feasibility of the Manggeng Peanut business at UD. Manggeng Food in Southwest Aceh Regency. This agro-industrial MSME plays a strategic role in driving the local economy, but faces challenges from fluctuating raw material prices and supplies that impact cash flow instability. This quantitative descriptive study uses primary and secondary data from production activities in 2024 to evaluate the profitability and feasibility of the business. The analysis results show that this business is profitable with revenue of Rp. 195,437,334. The Revenue Cost (R/C) Ratio of 1.30 indicates business feasibility, where every Rp. 1,000 expenditure generates IDR . 1,300 in revenue. The Break Even Point (BEP) analysis supports these findings, showing that the actual selling volume and price of all product variants far exceed the break-even point, with the highest profit margin in the 1.3 kg package. It is concluded that the Manggeng Peanut business at UD. Manggeng Food is not only financially viable but also has a resilient financial foundation and profitable prospects for further development, despite the volatility of raw materials.